Mitochondrial Cristae Morphology Reflecting Metabolism, Superoxide Formation, Redox Homeostasis, and Pathology - Ježek, Petr; Jabůrek, Martin; Holendová, Blanka; Engstová, Hana; Dlasková, Andrea (Antioxidants & redox signaling, 2023)
Significance: Mitochondrial (mt) reticulum network in the cell possesses amazing ultramorphology of parallel lamellar cristae, formed by the invaginated inner mitochondrial membrane. Its non-invaginated part, the inner boundary membrane (IBM) forms a cylindrical sandwich with the outer mitochondrial membrane (OMM). Crista membranes (CMs) meet IBM at crista junctions (CJs) of mt cristae organizing system (MICOS) complexes connected to OMM sorting and assembly machinery (SAM). Cristae dimensions, shape, and CJs have characteristic patterns for different metabolic regimes, physiological and pathological situations. Recent Advances: Cristae-shaping proteins were characterized, namely rows of ATP-synthase dimers forming the crista lamella edges, MICOS subunits, optic atrophy 1 (OPA1) isoforms and mitochondrial genome maintenance 1 (MGM1) filaments, prohibitins, and others. Detailed cristae ultramorphology changes were imaged by focused-ion beam/scanning electron microscopy. Dynamics of crista lamellae and mobile CJs were demonstrated by nanoscopy in living cells. With tBID-induced apoptosis a single entirely fused cristae reticulum was observed in a mitochondrial spheroid. Critical Issues: The mobility and composition of MICOS, OPA1, and ATP-synthase dimeric rows regulated by post-translational modifications might be exclusively responsible for cristae morphology changes, but ion fluxes across CM and resulting osmotic forces might be also involved. Inevitably, cristae ultramorphology should reflect also mitochondrial redox homeostasis, but details are unknown. Disordered cristae typically reflect higher superoxide formation. Future Directions: To link redox homeostasis to cristae ultramorphology and define markers, recent progress will help in uncovering mechanisms involved in proton-coupled electron transfer via the respiratory chain and in regulation of cristae architecture, leading to structural determination of superoxide formation sites and cristae ultramorphology changes in diseases. Antioxid. Redox Signal. 39, 635-683.
Keywords: MICOS; respiratory chain supercomplexes; Oxidation-Reduction; oxidace-redukce; Superoxides; Mitochondrial Membranes; OPA1; Homeostasis; adenosintrifosfát; Adenosine Triphosphate; mitochondrial superoxide formation; homeostáza; ATP-synthase dimeric rows; mitochondrial cristae; Mitochondrial Proteins; mitochondriální membrány; mitochondriální proteiny; superoxidy